Simulation of heat-mass transportation characteristics for removal of CO in a liquid nitrogen wash sieve plate column. (March 2020) - Haonan, Zhang; Cunquan, Zhang; Meng, Zhang; Peng-cheng, Song
Highlights: Dynamics modeling of heat-mass transportation processes for liquid nitrogen wash. Modeling of the efficiency of sieve plate heat-mass transportation process. Discussion of CFD simulations in detail through modeling a single sieve plate. Designing applicable material data and operating conditions. ASPEN PLUS simulation for effective removal of major harmful substances. Abstract: The liquid nitrogen wash process and sieve plate columns have been popular for removal of deleterious impurities (primarily including carbon monoxide) in chemical raw gas. It is of great guiding significance for precise description of distribution of components in column plates and phase variation rules, and prediction of column plate efficiency for optimization of operating conditions and geometric structure dimensions. A mathematical model of velocity field of gas and liquid in an industrial grade distillation sieve plate column was established and the corresponding CFD model was also presented to study flow characteristics of gas and liquid and the separation efficiency; those simulation results such as CO flow field, concentration variation and single plate separation efficiency were discussed; in addition, comparative analysis was carried out with reference to those classic experimental results. Our ASPEN PLUS simulation is carried out for effective removal of primary impurities (CO, CH4 and Ar), which can be removed to below 1 ppm, 1 ppm and 18 ppm through extraction and distillation of 50 plates, respectively. Thus, the requirements of the process standard may be satisfied. Results indicate that the important advantage of the simulation is that those influence factors may be automatically taken into account. It is investigated our simulation results are realistic and reliable to a certain degree to provide powerful technical support for practical engineering design.